A Kearifan Lokal dalam Tradisi Keislaman : Memahami Kontribusi Budaya Islam di Indonesia: Local Wisdom in Islamic Traditions: Contributions to Islamic Culture in Indonesia from the Perspective of Islamic Education - Maulidin, Syarif; Nopriyadi; Latif Nawawi, Muhamad (ISEDU : Islamic Education Journal, 2024)
This research is aiming to examine the process of Islam's adaptation to local culture in Indonesia, which is creating a distinct and unique Islamic identity. Islam, which is arriving in Indonesia as a global religion, is experiencing dynamic interaction with local traditions and cultures, resulting in syncretism in various aspects of society. Through a qualitative approach using literature study method, this research is finding that Islam in Indonesia is not only being passively accepted, but is undergoing deep negotiation and transformation, both in religious practices, social structures, arts, and law. One of the main findings is the integration between Islamic teachings and local cultural practices, such as in religious rituals, performing arts, and architecture, which is showing a strong influence of local culture on the form of Islam developing in Indonesia. However, this research is also revealing the tensions between more universal Islamic teachings and the more particular local cultural values, which are sometimes creating challenges in maintaining harmony between the two. This research is concluding that Islam in Indonesia is the result of a complex adaptation process, involving cultural syncretism that is not only creating harmony but also sometimes generating tensions. For further research, it is being suggested to explore more the regional differences in the acceptance of Islam and how this adaptation process is unfolding in different areas of Indonesia. Keywords: Islam, local culture, adaptation, syncretism, Indonesia